Predictors of physical activity among government servants in Malaysia - Ismail, Suriani; Mohd Zulkefli, Nor Afiah; Shaarin, Mohamad Takyuddin; Zainol Abidin, Nur Farzana; Tee, Siew Li (Community Health Society Malaysia, 2014)
Introduction: Work has become increasingly inert in nature especially for those who work in offices. This lack of physical activity could increase health risks. Moreover, readiness to perform physical activity is influenced by many factors including socio-demographic and socioeconomic characteristics and therefore it needs to be deliberated. Aim of the study is to determine the prevalence and determinants of physical activity among a group of government servants. Methods: This was a cross sectional study among a group of government servants using a self- administered questionnaire. Level of physical activity was assessed using a Malay version of International Physical Activity Questionnaire (IPAQ). Results: A total of 203 respondents participated. Majority of the respondents were in the moderate and high physical activity categories (59.6% and 25.6% respectively). There was a significant association between physical activity with gender and income (P<0.01), however no significant predictor was identified. Although not statistically significant, the OR was higher in females compare to males OR 1.16 (95% CI:0.46, 2.888), non-Malays compared to Malays OR 1.95 (95%CI:0.20,19.44), age group 40-59 compared to 20-39 years OR 1.34 (95%CI:0.55, 3.25), income >RM 5000 compared to income RM 1000-4999 OR 1.89 (95%CI0.73,4.88), those with tertiary education compared to primary and secondary education OR 1.94 (95%CI:0.47,2.37), and officers compared to supporting staff OR 1.55 (95%CI:0.70,3.45). Conclusions: Results show 14.8% of respondents were low in physical activity and that certain groups were at higher risk of low physical activity.